Analytical characterisation of axial shortening due to creep of reinforced concrete columns in tall buildings. (1st February 2021) - Muñoz Blanc, Carlos; Obiol Sánchez, Agustín; Fortea Navarro, Inma
Highlights: Polynomial for the characterization of axial shortening in tall building columns. It is evaluated in preliminary design stages with a polynomial approach. A typical two week construction process is considered. Concrete strength and amount of reinforcement are the most relevant parameters. Abstract: This paper proposes a new methodology to analyse how creep affects to reinforced concrete columns of tall buildings with central core that range between 20 and 40 floors. Creep shortening is due to compression stresses and are the different stress values between central core and columns which produces a differential shortening and a relevant bending moment increase in main structural elements. In the first place, it is shown how axial shortening due to creep affects to a 30-storey tall building based on the formulation included in Eurocode. All parameters that influence the behaviour under this phenomenon have been fixed. Afterwards, the polynomial that characterizes creep in this building is defined and, in the last place, it is analysed how variables such as concrete strength or the amount of reinforcement affect to long term shortening. These variables are included in the in the initial algorithm with different correction parameters.